Fenomena Perluasan Makna dalam Interaksi Penutur Bahasa Indonesia di Media Sosial X (Januari—Juli 2024): Analisis Semantik - Laksono, Wahyu; Nurhayati, Endang (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study aims to see language change in the form of meaning expansion between Indonesian speakers on social media X in the period January to July 2024. This qualitative research uses the method of listening and recording to collect data from the interaction of Indonesian speakers. The results of this study show that there are 11 data found to have experienced changes in the meaning of language in the expansion of meaning. The most frequently found causal factors are social and cultural change factors, then previous meaning associations and differences in areas of use. The three causal factors for the expansion of meaning with each data are as follows: 1) association factors totaling 3 data, namely in the words "goreng", "sampah", and "binatang"; 2) factors of differences in areas of use totaling 3 data, namely in the words or lexemes "najis", "receh/recehan", and "matang"; 3) social and cultural changes totaling 5 data, namely in the words "sepuh", "aman", "garing", "jompo", and "drama".The most common causative factors found are social and cultural change factors, then previous meaning associations and differences in fields of use.